Extrapulmonary tuberculosis - A cross-sectional study comparing the utility of Ziehl-Neelsen stain and immunohistochemistry - Veera Raghavan Gurusamy; Kanimozhi Sundararajan; Gowri Prakasam; Vincy TM (Asian Journal of Medical Sciences, 2024)
Background: Tuberculosis (TB) continues to be a significant global health issue despite known causes and effective treatments. Factors such as virulent strains, drug resistance, and the human immunodeficiency virus pandemic, especially in India, contribute to its prevalence. Mycobacterium tuberculosis, the TB agent, can evade immune responses, persisting within host cells. A distinct feature of TB, granuloma formation, can also appear in diseases such as leprosy, histoplasmosis, and non-infectious conditions like Crohn’s disease. Proper diagnosis is vital, as in resource-limited countries, TB treatment often relies on presumptive diagnoses based on imaging and symptoms, leading to high false positive rates. Aims and Objectives: This study aims to compare the utility of Ziehl-Neelsen (ZN) staining and immunohistochemistry (IHC) staining in suspected extrapulmonary TB lesions. Materials and Methods: This is a retrospective cross-sectional study conducted at the Institute of Pathology, Rajiv Gandhi Government General Hospital, Chennai, over a 2-year period from August 2015 to July 2017. Fifty cases out of the 198 suspected extrapulmonary TB lesions were selected for the study. Results: About 12% of cases were positive for acid-fast bacilli by ZN staining, whereas 82% of cases were positive for acid-fast bacilli by IHC staining. P value was found to be <0.001 by McNemar test which was statistically significant. Conclusion: Diagnosing extrapulmonary TB can be challenging because the disease presents with various clinical manifestations and the bacterial load may be low. Immunohistochemistry is superior to ZN staining for localization of the tubercle bacilli and thus can serve as an effective ancillary technique in diagnoses of extrapulmonary TB in formalin-fixed paraffin embedded tissue sections.